Pelatihan Pembuatan Kuis Interaktif Menggunakan Ispring Suite dan Kahoot Bagi Guru-Guru SMAN 2 Gerung Lombok Barat - Syahrul Azmi; Amrullah Amrullah; Baidowi Baidowi; Nani Kurniati; Eka Kurniawan (Pendidikan Matematika, FKIP Universitas Mataram, 2023)
This community service activity is in the form of interactive quiz-making training using the Ispring and Kahoot platforms. This service activity aims to a) Provide an overview of the use of the Ispring suite and Kahoot! software applications. to create interactive quiz questions that can be used as an interesting and fun evaluation tool for students, and b) Provide training on how to create interactive quiz questions using the Ispring Suite and Kahoot! software applications. for teachers at SMAN 2 Gerung West Lombok. The method used is lectures to explain the material, followed by questions and answers and practice. The team also gave tests (pretest and posttest). From the results of the activity, a product is produced in the form of an interactive quiz made using the Ispring or Kahoot applications. In addition, there is an increase in teachers' understanding of the material provided. This can be seen from the percentage of correct answers in the pretest of 32.63%, and the results of the posttest showed the percentage of correct answers to be 64.67%. Based on the results of the activity, it can be concluded that this community service activity is felt to be very useful in increasing the knowledge and skills of teachers on how to make interesting interactive quizzes so as to increase student enthusiasm and interest when participating in learning evaluation activities